How do you calculate this without Calculator?

Geometry Level 4

8 cos 2 π 7 ( 2 cos 2 2 π 7 + cos 2 π 7 1 ) + 1 = ? 8\cos \frac{2\pi}{7} \left( 2\cos^2 \frac{2\pi}7 +\cos \frac{2\pi}7 -1 \right) +1 = \, ?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

X = 8 cos 2 π 7 ( 2 cos 2 2 π 7 + cos 2 π 7 1 ) + 1 = 16 cos 3 2 π 7 + 8 cos 2 2 π 7 8 cos 2 π 7 + 1 = 4 ( 4 cos 3 2 π 7 3 cos 2 π 7 ) + 4 ( 2 cos 2 2 π 7 1 ) + 4 cos 2 π 7 + 5 = 4 ( cos 6 π 7 + cos 4 π 7 + cos 2 π 7 ) + 5 Note that cos ( π x ) = cos x = 4 ( cos π 7 + cos 3 π 7 + cos 5 π 7 ) + 5 See note: k = 0 n 1 cos ( 2 k + 1 2 n + 1 π ) = 1 2 = 4 ( 1 2 ) + 5 = 3 \begin{aligned} X & = 8\cos \frac {2\pi}7 \left(2 \cos^2 \frac {2\pi}7 + \cos \frac {2\pi}7 - 1\right) + 1 \\ & = 16 \cos^3 \frac {2\pi}7 + 8 \cos^2 \frac {2\pi}7 - 8 \cos \frac {2\pi}7 + 1 \\ & = 4\left(4\cos^3 \frac {2\pi}7 - 3\cos \frac {2\pi}7 \right) + 4\left(2\cos^2 \frac {2\pi}7 - 1\right) + 4 \cos \frac {2\pi}7 + 5 \\ & = 4\left(\cos \frac {6\pi}7 + \cos \frac {4\pi}7 + \cos \frac {2\pi}7 \right) + 5 & \small \color{#3D99F6} \text{Note that } \cos (\pi - x) = - \cos x \\ & = - 4\left({\color{#3D99F6}\cos \frac \pi 7 + \cos \frac {3\pi}7 + \cos \frac {5\pi}7} \right) + 5 & \small \color{#3D99F6} \text{See note: }\sum_{k=0}^{n-1} \cos \left( \frac {2k+1}{2n+1}\pi \right) = \frac 12 \\ & = - 4\left({\color{#3D99F6}\frac 12} \right) + 5 \\ & = \boxed{3} \end{aligned}


Note:

S = k = 0 n 1 cos ( 2 k + 1 2 n + 1 π ) = { k = 0 n 1 e 2 k + 1 2 n + 1 π i } = { e π i 2 n + 1 k = 0 n 1 e 2 k π i 2 n + 1 } = { e π i 2 n + 1 ( 1 e 2 n π i 2 n + 1 1 e 2 π i 2 n + 1 ) } = { e π i 2 n + 1 e π i 1 e 2 π i 2 n + 1 } = { e π i 2 n + 1 + 1 ( 1 + e π i 2 n + 1 ) ( 1 e π i 2 n + 1 ) } = { 1 1 e π i 2 n + 1 } = { 1 1 cos π i 2 n + 1 i sin π i 2 n + 1 } = { 1 cos π i 2 n + 1 + i sin π i 2 n + 1 ( 1 cos π i 2 n + 1 ) 2 + sin 2 π i 2 n + 1 } = { 1 cos π i 2 n + 1 + i sin π i 2 n + 1 2 2 cos π i 2 n + 1 } = 1 2 \small \begin{aligned} S & = \sum_{k=0}^{n-1} \cos \left( \frac {2k+1}{2n+1}\pi \right) \\ & = \Re \left \{ \sum_{k=0}^{n-1} e^{\frac {2k+1}{2n+1}\pi i} \right \} \\ & = \Re \left \{e^{\frac {\pi i}{2n+1}} \sum_{k=0}^{n-1} e^{\frac {2k\pi i}{2n+1}} \right \} \\ & = \Re \left \{e^{\frac {\pi i}{2n+1}} \left(\frac {1-e^{\frac {2n\pi i}{2n+1}}}{1-e^{\frac {2\pi i}{2n+1}}}\right) \right \} \\ & = \Re \left \{ \frac {e^{\frac {\pi i}{2n+1}}-e^{\pi i}}{1-e^{\frac {2\pi i}{2n+1}}} \right \} \\ & = \Re \left \{ \frac {e^{\frac {\pi i}{2n+1}} + 1}{\left(1+e^{\frac {\pi i}{2n+1}} \right) \left(1-e^{\frac {\pi i}{2n+1}} \right)} \right \} \\ & = \Re \left \{ \frac 1{1-e^{\frac {\pi i}{2n+1}}} \right \} \\ & = \Re \left \{ \frac 1{1-\cos \frac {\pi i}{2n+1} - i\sin \frac {\pi i}{2n+1}} \right \} \\ & = \Re \left \{ \frac {1-\cos \frac {\pi i}{2n+1} + i\sin \frac {\pi i}{2n+1}}{\left(1-\cos \frac {\pi i}{2n+1}\right)^2 + \sin^2 \frac {\pi i}{2n+1}} \right \} \\ & = \Re \left \{ \frac {1-\cos \frac {\pi i}{2n+1} + i\sin \frac {\pi i}{2n+1}}{2-2\cos \frac {\pi i}{2n+1}} \right \} \\ & = \frac 12 \end{aligned}

nice question and solution.. Did the same way....

Rahil Sehgal - 4 years, 3 months ago

Loved use of complex no. Not thought about that

Nivedit Jain - 4 years, 3 months ago

Let cos ( 7 x ) = cos 7 ( x ) 21 cos 5 ( x ) sin 2 ( x ) + 35 cos 3 ( x ) sin 4 ( x ) 7 cos ( x ) sin 6 ( x ) \cos(7x)=\cos^7(x)-21\cos^5(x)\sin^2(x)+35\cos^3(x)\sin^4(x)-7\cos(x)\sin^6(x)

As we can see that for x = 2 π 7 x=\frac{2\pi}{7} , LHS is 1 1 So RHS must be (lets write cos ( x ) = t \cos(x)=t

1 = t 7 21 t 5 ( 1 t 2 ) + 35 t 3 ( 1 t 2 ) 2 7 t ( 1 t 2 ) 3 1=t^7-21t^5(1-t^2)+35t^3(1-t^2)^2-7t(1-t^2)^3

Roots of this equation are cos ( 2 n π 7 ) \cos(\frac{2n\pi}{7}) where n n is 0 , 1 , 2 , 3 , 4 , 5 , 6 0,1,2,3,4,5,6 . Also n = 6 n=6 gives same result as n = 1 n=1 (As cos ( 2 π x ) = cos ( x ) \cos(2\pi-x)=\cos(x) And similarly for n=5 and n=4. This means that after removing t = 1 t=1 which is n = 0 n=0 , All the other roots are repeated twice. This means that we shall get a cubic squared.

Then after expanding all the terms in the centre equation, we get something like

0 = ( t 1 ) ( 8 t 3 + 4 t 2 4 t 1 ) 2 0=(t-1)(8t^3+4t^2-4t-1)^2

As x = 2 π 7 x=\frac{2\pi}{7} is a root, and it does not satisfy t 1 = 0 t-1=0 It must satisfy the cubic equation.

Thus , for x = 2 π 7 x=\frac{2\pi}{7} we have 4 t ( 2 t 2 + t 1 ) 1 = 0 4t(2t^2+t-1)-1=0

8 t ( 2 t 2 + t 1 ) + 1 = 3 8t(2t^2+t-1)+1=3

Hence proved.

For finding expansion of cos ( 7 x ) \cos(7x) and for finding the roots of the equation, I have used De Moivre's Theorem.

From this solution, we can see that x = 2 π 7 x=\frac{2\pi}{7} , x = 4 π 7 x=\frac{4\pi}{7} x = 6 π 7 x=\frac{6\pi}{7} are the 3 values for which the expression has the same answer i.e 3

Prakhar Bindal
Mar 4, 2017

pi/7 = x

8cos(2x)[cos4x+cos2x]+1

8cos(2x)[2cos3xcosx]+1

16cosxcos2xcos3x+1

note that cos3x = -cos4x

-16cosxcos2xcos4x+1

Now use the formula of product cosine series wherein angles are in GP

to get the product = -1/8

so answer is 2+1 = 3

Exactly I too did the same.Quite a simple way.

Spandan Senapati - 4 years, 2 months ago
Mark Hennings
Mar 6, 2017

If ζ = e 2 π i 7 \zeta =e^{\frac{2\pi i}{7}} then ζ 7 = 1 \zeta^7 = 1 and ζ 1 \zeta \neq 1 , so that ζ 6 + ζ 5 + ζ 4 + ζ 3 + ζ 2 + ζ + 1 = 0 \zeta^6 + \zeta^5 + \zeta^4 + \zeta^3 + \zeta^2 + \zeta +1 = 0 . Hence 0 = ζ 3 + ζ 2 + ζ + 1 + ζ 1 + ζ 2 + ζ 3 = ( ζ + ζ 1 ) 3 + ( ζ + ζ 1 ) 2 2 ( ζ + ζ 1 ) 1 = 8 c 3 + 4 c 2 2 c 1 = 4 c ( 2 c 2 + c 1 ) 1 \begin{aligned} 0 & = \zeta^3 + \zeta^2 + \zeta + 1 + \zeta^{-1} + \zeta^{-2} + \zeta^{-3} \; = (\zeta + \zeta^{-1})^3 + (\zeta+\zeta^{-1})^2 - 2(\zeta+\zeta^{-1}) - 1 \\ & = 8c^3 + 4c^2 - 2c - 1 \; = \; 4c(2c^2 + c - 1) - 1 \end{aligned} where c = cos 2 π 7 c = \cos\tfrac{2\pi}{7} . Thus 8 c ( 2 c 2 + c 1 ) + 1 = 2 × 1 + 1 = 3 8c(2c^2 + c - 1) + 1 \,=\, 2\times1+1 = \boxed{3} .

Nivedit Jain
Mar 3, 2017

2cos2π/7(cos4π/7+ cos2π/7) + 1 Used formula for cos2A Now use cosA+cosB = 2cos(A+B)/2 cos(A-B)/2 We get 16cos2π/7cos3π/7cosπ/7 +1 We get -16cosπ/7cos2π/7cos4π/7+1 Dividing and multiply by sinπ/7 We get on further solving using property of sin2A -2sin8π/7 ÷ sinπ/7 +1 We get 2+1 = 3

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...